VD_FINDINFO Jug / 2016 / 414 vom 14. Juni 2016 - VD Tribunal cantonal (2016)
FRAIS DE LA PROCÉDURE, PROCÉDURE ÉCRITE, INDEMNITÉEN GÉNÉRAL, PREMIÈRE INSTANCE | 426 al. 2 CPP (CH), 426 al. 3 CPP (CH), 429 al. 1 let. a CPP (CH)